Who Gets the Highest Return to Distance Higher Education? - Wang, Liang; Li, Fengliang (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2023)
The economics of distance higher education have not attracted enough attention. Few studies have analyzed the different returns to distance higher education at various income levels. Based on empirical analysis of data from China Family Panel Studies (CFPS), this study explored the differences of return to distance higher education at different income levels by using Mincer earnings function and quantile regression. Compared with face-to-face education, the study found that distance higher education brought considerable benefits to learners. While the return to face-to-face higher education has continued to decline, return to distance higher education has risen. Comparing the returns to distance education at different income levels showed that low-income groups obtained greater benefits from distance higher education, which can help to improve the income of vulnerable groups and promote social equality. China’s distance education institutions should promote the idea that distance higher education can improve the income growth of low-income groups, and increase the financial support for low-income groups to access distance higher education.